The Role of Fecal Fusobacterium nucleatum and pks+ Escherichia coli as Early Diagnostic Markers of Colorectal Cancer. (22nd November 2021) - Liu, Kaixi; Yang, Xinran; Zeng, Mi; Yuan, Yumeng; Sun, Jianhong; He, Ping; Sun, Jiayu; Xie, Qingdong; Chang, Xiaolan; Zhang, Suwei; Chen, Xiang; Cai, Leshan; et al.
Abstract : Background . Accurate analysis of intestinal microbiota will facilitate establishment of an evaluating system for assessing colorectal cancer (CRC) risk and prognosis. This study evaluates the potential role of Fusobacterium nucleatum ( F. nucleatum ) and Escherichia coli with a pks gene ( pks + E. coli ) in early CRC diagnosis. Methods . We recruited 139 patients, including CRC (n = 60 ), colorectal adenomatous polyposis (CAP) (n = 37 ), and healthy individuals (n = 42 ) based on their colonoscopy examinations. We collected stool and serum samples from the participants and measured the relative abundance of F. nucleatum and pks + E. coli in fecal samples by quantitative PCR. Receiver operating characteristic curve (ROC) analyses were used to analyze the diagnostic value of single or combined biomarkers. Results . Fecal F. nucleatum and pks + E. coli levels were higher in the CRC group in either the CAP group or healthy controls (P = 0.02 ; 0.01). There was no statistical difference in the distribution of F. nucleatum and pks + E. coli in patients with different tumor sites (P > 0.05 ). The combination of F. nucleatum + pks + E. coli +CEA+CA19-9+FOBT was chosen as the optimal panel in differentiating both CRC and CAP from the controls. The combination of F. nucleatum, pks + E. coli, and FOBT improved diagnostic efficiency. However, there was difficulty in differentiating CRC from CAP. Conclusion . Our results suggested that combining bacterial markers with conventional tumor markers improves the diagnostic efficiency for noninvasive diagnosis of CRC.